THE UTILIZATION OF U-DICTIONARY APPLICATION IN LEARNING VOCABULARY - Sheila Kamalia Hapsari (Dialectical Literature and Educational Journal, 2022)
Vocabulary is an important part of learning English. There are lots of ways to be able to have a lot of vocabulary, one of which is to use a U-Dictionary application. Students who are researching vocabulary have difficulties in mastering English, particularly in terms of getting to know vocabulary which they frequently research at school. This research aims to observe the utilization of U-Dictionary application in learning vocabulary at 7th grade of SMPN 6 Bekasi. A qualitative descriptive method was employed in this research. In this research, an interview with the English teacher at the school was conduct regarding the utilization of the U-Dictionary, a questionnaire for students regarding the benefits they get when using the U-Dictionary application, observations during classroom learning vocabulary activities, and documentation of students. Also, the data were obtained using questionnaire and interview. This research was conducted on 40 students who were given a questionnaire containing 10 statements regarding the benefits of the U-Dictionary. Most of the students 60% of 40 students are usually strongly agree that the U-Dictionary application helps the students in learning English Vocabulary, 52.5% of 40 students choose strongly agree that U-Dictionary application adds a lot of new vocabulary, 62.5% of 40 students are usually strongly agree that U-Dictionary application is necessary for the students. In observation of this research found 3 facts on the class; 1) maximum utilization and use can provide good things, 2) increase students learning enthusiasm, 3) give rewards to students.